PROBLEMS OF TEXT LINGUISTICS AS A KEY PROBLEM OF WORLD LINGUISTICS - Nigmatovna, Turniyazova Shakhnoza (International Journal of Membrane Science and Technology, 2023)
This article discusses the text and its linguistic status. The problems of text linguistics are inextricably linked with the transfer of units of the language system to speech, its real use in practice. The main issues of text linguistics, including the justification of speech units and their differentiation from language units, have not been seriously addressed in our research. Text syntax is on the verge of full scientific justification in the current period of development of linguistics. If it is fully justified, it should be called "big syntax", which differs sharply from ordinary syntax in terms of its object of investigation, namely, in which the relations between sentences, complex syntactic devices, paragraphs and chapters are checked.